Brassicaceous roots as an unexpected diversity hot-spot of helotialean endophytes - Jose G. Maciá-Vicente; Meike Piepenbring; Ondřej Koukol (IMA Fungus)
Abstract A high number of fungal strains were isolated from roots of Brassicaceae species collected across western and southern Europe, resulting in an unexpectedly rich collection of Cadophora species. These isolates enable us to present a new and comprehensive view of the ecological, morphological, and phylogenetic traits of root-inhabiting members of this helotialean genus. We provide phylogenetic placement of all of our isolates based on a four-gene dataset, analyze their phenotypic traits in relation to their phylogenetic relationships, and infer the potential distribution ranges of the species by sequence comparisons with available databases. We consider seven well supported phylogenetic lineages as species new to science. Six further lineages probably also represent new species but remain undescribed due to the lack of diagnostic morphological characters. Our results show that Cadophora, as currently circumscribed, is paraphyletic and encompasses a broad spectrum of morphologies and lifestyles. Among the new species, only two (C. ferruginea and C. constrictospora) form phialides and conidia typical of Cadophora, three species (C. echinata, C. gamsii and C. variabilis) produce chains of swollen hyphal segments that may function as holoblastic conidia, and one species (C. fascicularis) produces chains of holoblastic ramoconidia and conidia. Ancestral state reconstruction analysis suggests that phialidic conidiogenesis evolved several times in Cadophora s. lat. from a putatively holoblastic common ancestor. Most Cadophora lineages are rare as estimated from the availability of sequence data, in spite of having relatively wide distribution ranges, whereas five lineages may represent endemic relationships given their restricted distributions. Our dataset, probably the most comprehensive available for Cadophora, nevertheless shows knowledge gaps concerning the phylogenetic relationships within this genus and highlights a need for further investigation.